Gene copy-number variations (CNVs) of complement C4 and C4A deficiency in genetic risk and pathogenesis of juvenile dermatomyositis - Lintner, Katherine E; Patwardhan, Anjali; Rider, Lisa G; Abdul-Aziz, Rabheh; Wu, Yee Ling; Lundström, Emeli; Padyukov, Leonid; Zhou, Bi; Alhomosh, Alaaedin; Newsom, David; White, Peter; Jones, Karla B; et al. (Annals of the rheumatic diseases, 2016)
ObjectiveComplement-mediated vasculopathy of muscle and skin are clinical features of juvenile dermatomyositis (JDM). We assess gene copy-number variations (CNVs) for complement C4 and its isotypes, C4A and C4B, in genetic risks and pathogenesis of JDM.MethodsThe study population included 105 patients with JDM and 500 healthy European Americans. Gene copy-numbers (GCNs) for total C4, C4A, C4B and HLA-DRB1 genotypes were determined by Southern blots and qPCRs. Processed activation product C4d bound to erythrocytes (E-C4d) was measured by flow cytometry. Global gene-expression microarrays were performed in 19 patients with JDM and seven controls using PAXgene-blood RNA. Differential expression levels for selected genes were validated by qPCR.ResultsSignificantly lower GCNs and differences in distribution of GCN groups for total C4 and C4A were observed in JDM versus controls. Lower GCN of C4A in JDM remained among HLA DR3-positive subjects (p=0.015). Homozygous or heterozygous C4A-deficiency was present in 40.0% of patients with JDM compared with 18.2% of controls (OR=3.00 (1.87 to 4.79), p=8.2×10−6). Patients with JDM had higher levels of E-C4d than controls (p=0.004). In JDM, C4A-deficient subjects had higher levels of E-C4d (p=0.0003) and higher frequency of elevated levels of multiple serum muscle enzymes at diagnosis (p=0.0025). Microarray profiling of blood RNA revealed upregulation of type I interferon-stimulated genes and lower abundance of transcripts for T-cell and chemokine function genes in JDM, but this was less prominent among C4A-deficient or DR3-positive patients.ConclusionsComplement C4A deficiency appears to be an important factor for the genetic risk and pathogenesis of JDM, particularly in patients with a DR3-positive background.